A CONCEPTUAL FRAMEWORK OF RESISTANCE BEHAVIOR IN E-WASTE RECYCLING - Ahmad, Nur Hidayah (JOURNAL OF TOURISM, HOSPITALITY AND ENVIRONMENT MANAGEMENT (JTHEM), 2025)
This conceptual study applies Innovation Resistance Theory (IRT) to examine the behavioral barriers that limit household participation in formal e-waste recycling in Malaysia. Although environmental awareness is increasing, actual recycling behavior remains low, indicating a persistent gap between intention and action. The study identifies three primary functional barriers infrastructural inaccessibility, data security concerns, and institutional distrust that contribute to this resistance. It also explores the moderating role of social norms, which tend to have limited influence in the Malaysian context, where recycling is not yet embedded as a widely practiced or socially reinforced behaviour. By framing resistance as a deliberate response to perceived risks, inconveniences and trust, this study extends the application of IRT to the domain of sustainable behavior. The proposed framework integrates both structural and psychological barriers to explain why many households choose not to engage with formal recycling systems. This research offers theoretical contributions by advancing IRT within the context of environmental behavior and practical insights for policymakers. Addressing systemic weaknesses, improving institutional transparency, and designing culturally appropriate social norm interventions may help reduce resistance and support Malaysia’s national sustainability goals. The framework also provides a foundation for future empirical studies and targeted policy development.